Assessing the Efficacy of Consumer Boycotts of U.S. Target Firms: A Shareholder Wealth Analysis. - Tomlin, Kasaundra M. (Southern Economic Journal, 2019)
This article analyzes the effectiveness of 125 U.S. boycotts from 1978 to 2017. On average, the results suggest that actual consumer boycott calls against U.S. target firms (treatment firms) had a negative and statistically significant effect on the shareholder wealth of U.S. target firms. The synthetic control method and the placebo tests confirmed that the negative cumulative abnormal returns (CAR) observed here are robust and not due to idiosyncratic shocks unrelated to the announced boycotts. Negative and statistically significant boycott effects were also found for boycott threats and categorical issues related to union issues, animal rights, living wages in less‐developed countries, racial/sexual discrimination, ideological issues, and political/religious boycotts. The results also show that firms with a higher level of competition and advertising activity experienced larger negative boycott effects; and firms with higher net income observed mitigated boycott effects.